Phytochemical characterization, anti-cancer and antimicrobial activity of isolated fractions of Alysicarpus vaginalis - Tapadiya, Ganesh; Kale, Mayura A.; Saboo, Shweta (Bangladesh Journal of Pharmacology, 2017)
The methanolic extract of Alysicarpus vaginalis was selected for fractionation due to its known reported biological activity. The four fractions were separated and subjected for in vitro antimitotic and anti-proliferative assays along with anti-cancer activity on two human cancers cell lines (SK-MEL-2 and Hep-G2). The antimicrobial potential of fractions had been evaluated against bacteria and fungi. From all fractions, acetone and n-butanol fractions were effective against the cell lines. They show strong inhibitory action with mitotic index 6.2 and 8.4 mg/mL and IC50 values of anti-proliferative assay in between 19.7 to 14.2 mg/mL respectively, which was found to be comparable to the standard methothrexate 5.9 mg/mL and 13.2 mg/mL respectively. In antimicrobial activity, the zone of inhibition had been observed in the range of 12-27 mm and MIC value was found in the range of 0.2-0.1 mg/mL. The acetone fraction was found to be most active against fungi, and E. coli whereas chloroform and n-butanol fractions were more effective against S. aureus and B. subtilis. The phytochemical characterization by HPLC analysis indicated the presence of important polyphenolic and steroidal compounds. Video Clip of Methodology: Method: 8 min 16 sec Full Screen Alternate